Improvement and Implementation of Transformative Cultural Education Management Programs - Sundari, Susan (EDUMALSYS Journal of Research in Education Management, 2023)
This paper use a mixer methodology is employed, incorporating both a literature review and field studies. The central theme focuses on the management of Education Culture, including its historical development, conceptual framework, and the implementation of transformative iseducation. This paper aims to address three fundamental questions: firstly, what is the concept of Cultural Management in regard to Education? Secondly, what is the history and conception of education management, as well as transformative culture, within the context of Indonesia? Lastly, what contributions does education management make to the transformation of culture within the education sphere in Indonesia. Additionally, this document emphasizes the crucial role of teacher supervision as a definitive process. Moreover, it highlights the integration of culture as an inseparable component of the local community, deeply intertwined with the community's language. Culture (often called local wisdom) will be passed down through generations through oral stories. Education based on truth and nobility, distancing oneself from unreal thoughts, even far from the origins of unpleasant behavior or influence. Leadership education is important for moral (character)/ethics is easy), then the soul (emotional realm) is not only a cognitive and psychomotor realm, but synergizes with culture, education, and tourism, and needs to be developed in a coordinated mannerin education with real regional characteristics.